La géographie dans le programme d’enseignement des sciences sociales au niveau primaire et secondaire - Scarfe, N. (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1957)
Geography, being one of the social studies, has a unique contribution, a particular point of view to bring to bear in understanding Society. Its specific Junction is to train future citizens to imagine the conditions of the great world stage and so help them to think sanely about political and social conditions in the world around. Geography is the only subject that deals directly and fully with the influence of the physical environment upon human action and life. The author stresses the point that History and Geography are equally important and need to be given the same amount of time in the curriculum. But History and Geography are note the same : both are different ways of interpreting facts. In stressing the distinction between History and Geography, the author wishes to improve the teaching of both History and Geography, but as different disciplines. Finally the author points out that Geography progresses in difficulty and sequence, like arithmetic, so that one year is a prerequisite of the geographical concepts to be introduced in the next year of study. Geography is more appealing and more real to children than many other social sciences and so more stimulating to intellectual effort.